Application of The Extended Theory of Planned Behavior on Shallot Farmers In Adopting Semi-Organic Farming Method - Ibrahim, Taris; Perwitasari, Hani; Masyhuri (HABITAT, 2024)
Environmental issues today are driving consumer behavior toward choosing products with minimal chemical content. This trend puts pressure on farmers to meet consumer demand through semi-organic farming methods. It implies that products from semi-organic farming have a promising future. However, farmers' interest in adopting semi-organic farming methods remains relatively low, as indicated by the slow adoption process. The aim of this research is to examine the influence of attitudes, subjective norms, perceived behavioral control, environmental concern, and environmental knowledge on the intention to adopt semi-organic farming methods, both directly and through the mediation of attitudes. This study is descriptive and verifiable, involving 136 shallot farmers as respondents from Kretek and Sanden Districts, Bantul Regency. The sample was determined using purposive sampling, and the analysis was conducted using SEM-PLS techniques. The results show that attitudes, subjective norms, and perceived behavioral control have a positive and significant effect on the intention to adopt semi-organic farming methods. Environmental concern and environmental knowledge do not directly affect the intention to adopt semi-organic farming methods, but they must influence attitudes in order to impact the intention to adopt semi-organic farming methods.